Riverblindness in Africa : Taming the Lion's Stare - Benton, Bruce, 1942- (Book collections on Project MUSE., 2020)
"The World Bank coordinated a fight against riverblindness, a parasitic tropical disease, which commenced more than forty years ago. The story of the battle has an epic scale, both in terms of geography and the number of people and organizations involved. The book provides a success story and a bureaucratic template for other global health efforts. The author worked for the World Bank and oversaw its campaign to end riverblindness"--